UJI FITOKIMIA DAUN KAYU MANIS (Cinnamomum cassia) DARI GUNUNG LINTANG - Ganjar Satria Andika S; Budi Sutiya; Trisnu Satriadi (Jurnal Sylva Scienteae, 2025)
This research aims to determine the potential of chemical compounds contained in cinnamon (Cinnamomum cassia) by carrying out phytochemical tests. Analyze the phytochemical content of cinnamon leaves based on the position of the leaf, namely the tip/shoot, middle and base of the leaf. Analyzing the phytochemical content of cinnamon leaves based on location/land cover. This research was carried out for 2 months in the wood science laboratory of the Faculty of Forestry, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The cinnamon leaf samples studied were taken from Gunung Lintang, Martadah village, Tambang Re district, Tanah Laut district, South Kalimantan. Test result data by giving a plus two sign (++) if it contains active chemical compounds (strong/sharp indication), giving a plus one sign (+) if it contains active chemical compounds (weak indication), not detected/not containing active chemical compounds in it will be marked with a minus (-), then analyzed descriptively. Tabulation of data from observations of phytochemical tests on cinnamon leaves which observed flavonoids, saponins, quinones, tannins, steroids, triterpenoids, alkaloids. The research results show that cinnamon that grows under stands has phytochemical compounds in the leaves. The results of phytochemical tests on the leaves were characterized by the presence of saponin (+), quinone (-), steroid (+), alkaloid (+) compounds. The results of qualitative phytochemical tests on cinnamon leaves in the open were flavonoids (-), saponins (+), quinones (-), tannins (-), steroids (+), while the middle and base of the leaves indicated (++) triterpenoids (-), alkaloids in the shoot, middle and base are indicated (+).Penelitian ini bertujuan untuk mengetahui potensi senyawa kimia yang terkandung dalam kayu manis (Cinnamomum cassia) dengan melakukan uji fitokimia. Menganalisis kandungan fitokimia daun kayu manis berdasarkan kedudukan daun yakni ujung/pucuk, tengah dan pangkal daun. Menganalisis kandungan fitokimia daun kayu manis berdasarkan lokasi/tutupan lahan. Penelitian ini dilaksanakan selama 2 bulan di laboratorium ilmu kayu Fakultas kehutanan Universitas Lambung Mangkurat Banjarbaru Kalimantan selatan. sampel daun kayu manis yang diteliti diambil dari gunung lintang, desa Martadah kecamatan Tambang ulang kabupaten Tanah laut Kalimantan selatan. Data hasil pengujian memberi tanda plus dua (++)terdapat kandungan senyawa kimia aktif di dalamnya (indikasi kuat/tajam), memberi tanda plus satu (+) apabila kandungan senyawa kimia aktif di dalamnya (indikasi lemah), tidak terdeteksi/tidak mengandung senyawa kimia aktif di dalamnya akan ditandai dengan minus (-), kemudian dianalisis secara deskriptif. Tabulasi data hasil pengamatan uji fitokimia daun kayu manis yang di amati flavonoid, saponin, quinon,tanin, steroid, triterpenoid, alkaloid. Hasil penelitian menunjukan bahwa kayu manis yang tumbuh di bawah tegakan memiliki senyawa fitokimia pada bagian daunya. Hasil uji fitokimia pada daun ditandai dengan adanya senyawa saponin (+), quinon (-), steroid (+), alkaloid (+). Hasil uji kualitatif fitokimia pada daun kayu manis di tempat terbuka flavonoid (-), saponin (+), quinon (-), tannin (-), steroid (+), sedangkan bagian tengah dan pangkal daun indikasi (++) triterpenoid (-), alkaloid bagian pucuk, tengah dan pangkal indikasi (+)